CYP3A activity in severe liver cirrhosis correlates with Child–Pugh and model for end‐stage liver disease (MELD) scores. (January 2014) - Albarmawi, Albader; Czock, David; Gauss, Annika; Ehehalt, Robert; Lorenzo Bermejo, Justo; Burhenne, Jürgen; Ganten, Tom M.; Sauer, Peter; Haefeli, Walter E.
<x xml:space="preserve">Abstract</x> Aims Impaired liver function often necessitates drug dose adjustment to avoid excessive drug accumulation and adverse events, but a marker for the extent of the required adjustment is lacking. The aim of this study was to investigate whether Child–Pugh (CP) and model for end‐stage liver disease (MELD) scores correlate with drug clearance. Methods Midazolam was used as a CYP3A probe and its pharmacokinetics were analyzed in 24 patients with mild to severe liver cirrhosis (n = 4, 10 and 10 with CP class A, B and C, respectively) and six patients without liver disease. Results Both scores correlated well with unbound midazolam clearance (CLu), unbound midazolam fraction and half‐life (all P < 0.01), whereas the unbound steady‐state volume of distribution was not significantly changed. In patients with severe liver cirrhosis unbound midazolam clearance was only 14% of controls (CP C: CLu = 843 ± 346 l h−1, MELD ≥ 15: CLu = 805 ± 474 l h−1, controls: CLu = 5815 ± 2649 l h−1, P < 0.01). Conclusion The correlation with unbound midazolam clearance suggests that either score predicts the metabolic capacity of CYP3A, the most relevant drug metabolizing enzyme subfamily in humans.